The importance of diversity, equity, and inclusion in veterinary medicine: advocacy through art - Negron, Justine Adrianna, author; Aubry, Lise, advisor; Blanco, Cristina, committee member; Sadar, Miranda, committee member (Colorado State University. Libraries, 2025)
Veterinary medicine has traditionally faced a lack of racial and ethnic diversity in its workforce. Despite ongoing efforts to minimize this issue, such as American Veterinary Medical Association diversity symposia and recruitment efforts by veterinary schools, 'Diversity, Equity and Inclusion' continues to be a modern challenge for the field. This honors thesis aims to answer the following: Why does racial and ethnic diversity in veterinary medicine matter? By using private organizational research, government statistics, interdisciplinary journal articles, and books, this project argues that diversity in veterinary medicine matters for three reasons: i) enabling better client-provider communication via diverse perspectives and cultural competency, ii) creating increased profitability and thus financial security for veterinary business institutions, and iii) allowing for better understanding/problem-solving of complex issues, which could impact society in sectors like public health. Given that visual art can cross cultural and language barriers to convey ideas and mobilize societies, three paintings were created to further communicate these themes. Taken together, the written and artistic components are meant to serve as educational tools, aiming to promote continued research and efforts toward increasing veterinary diversity to bolster the profession's relevance in serving today's communities.
Colorado State University, College of Natural Sciences-Department of Biology, Warner College of Natural Resources-Department of Fish, Wildlife, and Conservation Biology, College of Veterinary Medicine and Biomedical Sciences-Department of Avian, Exotic, and Zoological Medicine.
Image 1. Diversity and collaboration-creating better solutions; Image 2. Diversity and communication-two sides, one goal; Image 3. Diversity and profitability-building a sustainable future.
Keywords: veterinary medicine; diversity, equity, and inclusion; art; visual art